Transformational Leadership Effect on Organizational Performance in Ethiopia Public Sector: Systematic Literature Review - Shashi Kant; Kenenisa Lemi DEBELA; Kebede Asefa (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
The knowledge of constructivism in the style of transformational leadership as it pertains to organizational performance was thoroughly reviewed to produce the current study. It studies the function of transforming leadership and investigates a number of problems that may arise in organizations under such circumstances. A systematic review and subsequent thematic content analysis of the literature, including findings from existing literature and research papers that have been published, is used to establish the theoretical underpinnings. They were thoroughly reviewed, and the best materials that matched them were then carefully picked out and included in order to reach a conclusion. The outcome highlights the need for managers to use a transformational leadership style to put into practice cutting-edge tactics for employee empowerment so they can navigate the environment of rapid change and perform to their full potential. A conceptual qualitative framework based on PRISMA was constructed and advised for the functionalism of personalized transformational leadership style to involve stakeholders in amicably avoiding recalcitrance. The forest plot and funnel plot were used to check the combined effect size and publication bias. This strategy can assist transformational leadership managers in identifying opportunities during this crisis and assisting them in drawing important conclusions about how to address problems and foster a healthy culture. This paradigm can assist a transformational leader in managing stakeholders' expectations and benefit both academics and practitioners by working collaboratively to solve anticipated challenges. Limitations include bias risks such selective result reporting, inadequate blinding, attrition bias, and selection bias. Research novelty was a fresh idea that might provide new knowledge or add to the body of knowledge currently in existence.